2013
DOI: 10.1111/ijac.12198
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Valve Made in Low‐Temperature Co‐Fired Ceramics

Abstract: This article describes the technology of the electromagnetic valve made in the LTCC (low temperature co‐fired ceramics). The actuation is supplied by mutual reaction between a 3D coil and a neodymium magnet bonded to flexible membrane. Such solution has many advantages like small power consumption and relatively great attractive forces. The valve is built in a hybrid polymer‐ceramic technology. The microfluidic and coil parts are fabricated in the LTCC technology. The flexible section is manufactured using a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
1
0
3
Order By: Relevance
“…The performed analysis has shown that after treatment, oxygen content in LTCC and PDMS increased, which seems to indicate the presence of oxygen radicals and silanol groups (Si-OH) (Morent et al , 2007; Kim and Jeong, 2011; Lee and Yang, 2012). On the basis of the LTCC-PDMS bonding experiment, a few microfluidic systems [microvalve (Czok et al , 2014), micropump (Czok et al , 2014), micromixer (Malecha and Malecha, 2014) and fluorescent sensor] have been developed. In this paper, the design, fabrication and performance of the microfluidic fluorescent sensor that has been constructed using hybrid LTCC-PDMS technology is presented.…”
Section: Introductionmentioning
confidence: 99%
“…The performed analysis has shown that after treatment, oxygen content in LTCC and PDMS increased, which seems to indicate the presence of oxygen radicals and silanol groups (Si-OH) (Morent et al , 2007; Kim and Jeong, 2011; Lee and Yang, 2012). On the basis of the LTCC-PDMS bonding experiment, a few microfluidic systems [microvalve (Czok et al , 2014), micropump (Czok et al , 2014), micromixer (Malecha and Malecha, 2014) and fluorescent sensor] have been developed. In this paper, the design, fabrication and performance of the microfluidic fluorescent sensor that has been constructed using hybrid LTCC-PDMS technology is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Em 2014, Czok et al [CZOK et al, 2014] apresentaram o desenvolvimento de uma microválvula eletromagneticamente atuada, fabricada utilizando a tecnologia LTCC usando uma membrana fabricada em PDMS (figura 14). Uma membrana circular com 300 µm de espessura foi fabricada em um molde feito usando fitas cerâmicas de LTCC.…”
Section: Microválvulas Eletromagnéticasunclassified
“…Mag. [TERRY et al, 1979;YANAGISAWA et al, 1995;MECKES at el., 1995;BAE at el., 2003;FU et al, 2003;KRUSEMARK et al, 1998;OH et al, 2001;AHN et al, 1999;AHN et al, 2005;CASALS-TERRÉ et al, 2008;CAI at el., 2014;DUCLOUX et al, 2009;Chang et al, 2014;GONGORA et al, 1999;CZOK et al, 2014;CHENG et al, 2008;GASPAR et al, 2008] Elet. GOLL et al, 1997;ROBERTSON et al, 1998;SCHAILBLE, 2001;WIJNGAART et al, 2002;YOBAS et al, 2001;PATRASCU et al, 2012;YILDIRIM et al, 2012] Piez.…”
Section: Tabela 1 Parâmetros De Projeto Da Microválvula Versus Métodunclassified
See 1 more Smart Citation